2017
DOI: 10.1098/rspb.2017.0391
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of feeding regime alters sexual dimorphism for lifespan and reduces sexual conflict in Drosophila melanogaster

Abstract: Sexual dimorphism for lifespan (SDL) is widespread, but poorly understood. A leading hypothesis, which we test here, is that strong SDL can reduce sexual conflict by allowing each sex to maximize its sex-specific fitness. We used replicated experimental evolution lines of the fruit fly, Drosophila melanogaster, which had been maintained for over 360 generations on either unpredictable ‘Random’ or predictable ‘Regular’ feeding regimes. This evolutionary manipulation of feeding regime led to robust, enhanced SDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…This content downloaded from 130.236.083.247 on March 22, 2019 08:57:58 AM quent replacement of competitor flies also likely explains why females had a shorter average life span than males in our experiments. In previous studies of our study population, we and others (e.g., Magwere et al 2004;Lehtovaara et al 2013;Griffin et al 2016;Duxbury et al 2017) have found that females outlive males. The degree of exposure to males does, however, have a large impact on survival of Drosophila melanogaster females (Partridge et al 1987;Friberg 2005;Lehtovaara et al 2013;Zajitschek et al 2013), and the fact that we replaced competitors more frequently than in any of the aforementioned studies therefore probably caused the shorter female life span.…”
Section: Genetic Quality and Sex-specific Aging 767supporting
confidence: 56%
“…This content downloaded from 130.236.083.247 on March 22, 2019 08:57:58 AM quent replacement of competitor flies also likely explains why females had a shorter average life span than males in our experiments. In previous studies of our study population, we and others (e.g., Magwere et al 2004;Lehtovaara et al 2013;Griffin et al 2016;Duxbury et al 2017) have found that females outlive males. The degree of exposure to males does, however, have a large impact on survival of Drosophila melanogaster females (Partridge et al 1987;Friberg 2005;Lehtovaara et al 2013;Zajitschek et al 2013), and the fact that we replaced competitors more frequently than in any of the aforementioned studies therefore probably caused the shorter female life span.…”
Section: Genetic Quality and Sex-specific Aging 767supporting
confidence: 56%
“…This was surprising, since in previous studies of this population we and others (e.g. Megwere et al 2004;Lehtovaara et al 2013;Carazo et al 2016;Griffin et al 2016;Duxbury et al 2017) have found that females outlive males. The degree of exposure to males does, however, have a large impact on survival of D. melanogaster females (Partridge et al 1987;Friberg 2005;Lethovaara et al 2013;Zajitschek et al 2013), and during the experiments we replaced competitor flies that focal individuals were housed with on a weekly basis.…”
Section: Discussionmentioning
confidence: 61%
“…; Duxbury et al. ) have found that females outlive males. The degree of exposure to males does, however, have a large impact on survival of D. melanogaster females (Partridge et al.…”
Section: Discussionmentioning
confidence: 97%
“…The sexually antagonistic selection that generates intralocus sexual conflict is widespread in natural populations (e.g., Cox & Calsbeek, ; Mainguy, Cote, Festa‐Bianchet, & Coltman, ) and has been detected in insects (e.g., Archer, Zajitschek, Sakaluk, Royle, & Hunt, ; Harano, Okada, Nakayama, Miyatake, & Hosken, ; Lewis, Wedell, & Hunt, ; Pischedda & Chippindale, ), vertebrates (Mokkonen et al, ), and plants (Delph et al, ). In addition to being taxonomically widespread, intralocus conflict has important and far‐reaching evolutionary effects, influencing demography (e.g., Berger et al, ; Katsuki, Harano, Miyatake, Okada, & Hosken, ), adaptation (e.g., Hawkes et al, ; Rostant, Kay, Wedell, & Hosken, ), life‐history strategies (e.g., Archer et al, ; Duxbury, Rostant, & Chapman, ), sex‐chromosome evolution (Mank et al, ), and speciation (Rice & Chippindale, ). Given the ubiquity of intralocus sexual conflict and its broad evolutionary impacts (reviewed in Bonduriansky & Chenoweth, ; van Doorn, ), it is important that we can accurately detect it and quantify its strength.…”
Section: Introductionmentioning
confidence: 99%